Integrating Local Culture into Mathematics Learning: Ethnomathematics Approach Using Udeng Pacul Gowang in Elementary Schools - Susanti, Rizky May; Gunansyah, Ganes; Nasution, Nasution (Papanda Publisher, 2025)
This study investigates the integration of Udeng Pacul Gowang, a traditional headgear from Sidoarjo, Indonesia, into elementary mathematics education through an ethnomathematics approach. The purpose of this research is to explore the cultural and historical significance of Udeng Pacul Gowang, analyze its aesthetic design crafted by local artisans, and utilize it as a meaningful learning resource to enhance students’ understanding of mathematical concepts. Using a descriptive qualitative method, the study gathered data through in-depth interviews with 12 local artisans and 8 elementary school educators, direct observations of the production process, and documentation review conducted over a three-month period from March to May 2025. The results indicate that Udeng Pacul Gowang incorporates various geometric shapes such as triangles, circles, and symmetrical patterns, which correspond to mathematical concepts including geometry, similarity, and measurement. Specifically, students were able to identify at least four types of geometric forms and apply measurement concepts through hands-on activities with the headgear. These cultural elements provide a contextualized and tangible learning experience that helps students relate abstract mathematical ideas to their everyday environment. Additionally, integrating Udeng Pacul Gowang in the learning process promotes students’ cultural pride and appreciation for their local heritage, which positively impacts their motivation and engagement in mathematics. The study highlights the potential of culturally responsive teaching to bridge the gap between academic knowledge and cultural identity, encouraging the development of a more holistic learning approach. Despite the limited formal curriculum incorporation of ethnomathematics, this research emphasizes the role of educators in innovating teaching strategies by embedding local cultural artifacts in classroom activities. This approach not only enriches the mathematics curriculum but also supports the preservation of local culture among younger generations. The findings suggest that Udeng Pacul Gowang can serve as an effective educational tool to foster both mathematical proficiency and cultural awareness in elementary schools.